Development of “Kids Athletics” Model on Children’s Gross Motor Skills and Self-Concept in Physical Education - Hb, Bafirman; Abas, Syamsuar; Nanda Putra, Rifki (International Journal of Psychosocial Rehabilitation, 2020)
The “Kids' Athletics” learning model is a multilateral physical activity. Students do a variety of physical activities such as running, throwing, jumping, and rolling, which are adjusted to the characteristics of the age level. Through training and events, the “Kids Athletics” model movements excite children so that they are involved in sport activities physically and psychologically. This study aims to examine how the “Kids Athletics” learning model influences children’s gross motor skills and self-concept. This Research and Development (R&D) design uses Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation (ADDIE) models. The validation design of this model was validated by motor experts, counselors, and language experts. The practicality of the model was validated by physical education teachers. The data were collected through the validity test, practicality test, and effectiveness test. The data were analyzed by using qualitative and quantitative descriptive percentage techniques. The results of the validity test obtained a mean of 80.8% (valid). The results of the practicality test obtained a mean of 93.6%. (practical). The results of the effectiveness test showed that the “Kids' Athletics” learning model effectively improved: (1) Children’s gross motor skills with Zobserved > Ztable (-4.790 > -0.00003) with significance () of 0.000 < 0.05; (2) children’s self-concept with Zobserved > Ztable (-3.736 > -0.0001) with significance () of 0.000 < 0.05. It can be interpreted that there is an increase in gross motor skill and self-concept between before and after the Kids' Athletics” learning model is carried out.